Astrocytes of the eye and optic nerve: heterogeneous populations with unique functions mediate axonal resilience and vulnerability to glaucoma - Cullen, Paul F.; Sun, Daniel (Frontiers in Ophthalmology, 2023)
The role of glia, particularly astrocytes, in mediating the central nervous system's response to injury and neurodegenerative disease is an increasingly well studied topic. These cells perform myriad support functions under physiological conditions but undergo behavioral changes -collectively referred to as 'reactivity' -in response to the disruption of neuronal homeostasis from insults, including glaucoma. However, much remains unknown about how reactivity alters disease progression -both beneficially and detrimentally -and whether these changes can be therapeutically modulated to improve outcomes. Historically, the heterogeneity of astrocyte behavior has been insufficiently addressed under both physiological and pathological conditions, resulting in a fragmented and often contradictory understanding of their contributions to health and disease. Thanks to increased focus in recent years, we now know this heterogeneity encompasses both intrinsic variation in physiological function and insult-specific changes that vary between pathologies. Although previous studies demonstrate astrocytic alterations in glaucoma, both in human disease and animal models, generally these findings do not conclusively link astrocytes to causative roles in neuroprotection or degeneration, rather than a subsequent response. Efforts to bolster our understanding by drawing on knowledge of brain astrocytes has been constrained by the primacy in the literature of findings from peri-synaptic 'gray matter' astrocytes, whereas much early degeneration in glaucoma occurs in axonal regions populated by fibrous 'white matter' astrocytes. However, by focusing on findings from astrocytes of the anterior visual pathway -those of the retina, unmyelinated optic nerve head, and myelinated optic nerve regions -we aim to highlight aspects of their behavior that may contribute to axonal vulnerability and glaucoma progression, including roles in mitochondrial turnover and energy provisioning. Furthermore, we posit that astrocytes of the retina, optic nerve head and myelinated optic nerve, although sharing developmental origins and linked by a network of gap junctions, may be best understood as distinct populations residing in markedly different niches with accompanying functional specializations. A closer investigation of their behavioral repertoires may elucidate not only their role in glaucoma, but also mechanisms to induce protective behaviors that can impede the progressive axonal damage and retinal ganglion cell death that drive vision loss in this devastating condition.